Development of Maize Hybrids With Enhanced Vitamin-E, Vitamin-A, Lysine, and Tryptophan Through Molecular Breeding - Das, Abhijit K.; Gowda, Munegowda M.; Muthusamy, Vignesh; Zunjare, Rajkumar U.; Chauhan, Hema S.; Baveja, Aanchal; Bhatt, Vinay; Chand, Gulab; Bhat, Jayant S.; Guleria, Satish K.; Saha, Supradip; Gupta, Hari S.; et al. (Frontiers in Plant Science, 2021)
Malnutrition is a widespread problem which affects human health, society and economy. Traditional maize that serves as an important source of human nutrition, is deficient in vitamin-E, vitamin-A, lysine and tryptophan. Here, favourable alleles of vte4 (α-tocopherol methyl transferase), crtRB1 (β-carotene hydroxylase), lcyE (lycopene ε-cyclase) and o2 (opaque2) genes were combined in parental lines of four popular hybrids using marker-assisted selection. BC1F1, BC2F1 and BC2F2 populations were genotyped using gene-based markers of vte4, crtRB1, lcyE and o2. Background selection using 81-103 simple sequence repeats (SSRs) markers led to recovery of recurrent parent genome up to 95.45%. Alpha (α)-tocopherol was significantly enhanced among introgressed progenies (16.13 µg/g) as compared to original inbreds (7.90 µg/g). Provitamin-A (proA) (10.42 µg/g), lysine (0.352%) and tryptophan (0.086%) were also high in the introgressed progenies. The reconstituted hybrids showed 2-fold enhancement in α-tocopherol (16.83 µg/g) over original hybrids (8.06 µg/g). Improved hybrids also possessed high proA (11.48 µg/g), lysine (0.367%) and tryptophan (0.084%) when compared with traditional hybrids. The reconstituted hybrids recorded mean grain yield of 8066 kg/ha, which was at par with original hybrids (mean: 7846 kg/ha). The marker-assisted selection (MAS) -derived genotypes resembled their corresponding original hybrids for majority of agronomic and yield related traits, besides characters related to distinctness, uniformity and stability (DUS). This is the first report of the development of maize with enhanced vitamin-E, vitamin-A, lysine and tryptophan.